A Novel Derivation Predicting Survival After Primary Tumor Resection in Stage IV Colorectal Cancer: Validation of a Prognostic Scoring Model and an Online Calculator to Provide Individualized Survival Estimation. Issue 9 (September 2017) - Tan, Winson Jianhong; Dorajoo, Sreemanee Raaj; Chee, Madeline Yen Min; Tan, Wah Siew; Foo, Fung Joon; Tang, Choong Leong; Chew, Min Hoe
Abstract : BACKGROUND: A prognostic scoring model has been devised previously to predict survival following primary tumor resection in patients with metastatic colorectal cancer and unresectable metastases. This has yet to be validated. OBJECTIVE: The main objectives of this study are to validate the proposed prognostic scoring model and create an interactive online calculator to estimate an individual's survival after primary tumor resection. DESIGN: Clinical data and survival outcomes of patients were extracted from a prospectively maintained database. Patients were categorized into good, moderate, or poor survivor groups based on the previously proposed scoring algorithm. Discrimination was assessed and recalibration was performed, with the recalibrated model implemented as an interactive Web application to provide individualized survival probability. SETTINGS: This study was conducted at a tertiary referral center. PATIENTS: The study included 324 consecutive patients with metastatic colorectal carcinoma and unresectable metastases who underwent primary tumor resection between January 2008 and December 2013. MAIN OUTCOME MEASURES: The primary outcome measured was overall survival. RESULTS: Three hundred twenty-four patients were included in the study. Median survival in the good, moderate, and poor prognostic groups was 56.8, 25.7, and 19.9 months (log rank test, p = 0.003). The κ statistic was 0.638 and R 2 D was 0.101. Significant differences in survival were found between the moderate and good prognostic groups (HR, 2.79; 95% CI, 1.51–5.15; p = 0.001) and between poor and good prognostic groups (HR, 4.12; 95% CI, 1.98–8.55; p < 0.001). The model was implemented as an interactive online calculator to provide individualized survival estimation after primary tumor resection (http://bit.ly/Stage4PrognosticScore ). LIMITATIONS: Selection bias and single-center data preclude the generalizability of the proposed model. Information regarding the severity or likelihood of developing symptoms from the primary tumor were also not accounted for in the prognostic scoring model proposed. CONCLUSIONS: The prognostic scoring model provides good prognostic stratification of survival after primary tumor resection and may be a useful tool to predict survival after primary tumor resection. SeeVideo Abstract athttp://links.lww.com/DCR/A330 .